What Is Jannah? - Zainab, Salmah umm (Goodword Books India, 2002)
Jannah, in Islamic belief, is the concept of paradise or heaven, described as a place of eternal bliss and reward for those who follow Allah's guidance. It is depicted as a beautiful garden filled with rivers, fruits, and peace, where inhabitants experience joy, comfort, and the presence of Allah. Jannah represents the ultimate goal for Muslims, symbolizing spiritual fulfillment and the reward for a righteous life on Earth.